Application of cartographic and censual tools In a historiographical study of the Central District of Barva, 1945-2014 - Otárola Guevara, Marcela (2017)
The study of cities, from a historiographical perspective, it benefits from the tools of other disciplines to understand the magnitude of the changes that occur in them. Therefore, a research in Urban History made in the Central District of Barva, city of Costa Rica, relied on the use of aerial photos, maps and population registers to understand its transformation from a rural setting to an urban one, between 1945 and 2014.  The use of mapping and census research tools will be showed in an Applied History research. As a result of its use, three periods were defined, each one with a different configuration, and a demographic transformation was exposed, thus observing the modification of the urban morphology as a direct action of the human being.